Examining Undergraduates’ Intentions to Pursue a Science Career: A Longitudinal Study of a National Biomedical Training Initiative - Jayashri Srinivasan; Krystle P. Cobian; Hector V. Ramos; Christina A. Christie; Catherine M. Crespi; Teresa Seeman (Education Sciences, 2025)
Disparities in the participation of individuals from historically excluded groups in science careers persist, particularly at advanced career stages. In response to this challenge, the National Institutes of Health developed the BUilding Infrastructure Leading to Diversity (BUILD) initiative, aimed at undergraduate institutions to examine evidence-based strategies to engage and retain students across science-related fields. In this longitudinal study, we used propensity score matching and mixed-effects logistic regression models to examine the effects of BUILD on undergraduates’ intentions to pursue science-related research careers. The results indicate that students who participated in BUILD are four times more likely to pursue a science-related research career in comparison to their non-BUILD counterparts. We also discuss and present the need to incorporate research training and mentorship to promote a diverse scientific workforce.